1983
DOI: 10.1136/hrt.50.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic, hormonal, and electrolyte effects of enalapril in heart failure.

Abstract: SUMMARY Enalapril, the new converting enzyme inhibitor, was administered to eight patients with heart failure (NYHA Functional Class II to IV) during standardised and intensive haemodynamic, hormone, and electrolyte monitoring. The first dose (5 mg) of enalapril induced a fall in plasma angiotensin II and noradrenaline levels, and prolonged decrements in systemic vascular resistance, arterial pressure, heart rate, and right heart pressures. Maximum haemodynamic effects were evident four to eight hours after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 9 publications
4
19
0
Order By: Relevance
“…The pooled hypertension (Rich et al, 1982). The reduction ilts from the international pilot studies on in pulmonary resistance in the present study lapril in congestive heart failure ( Figure 8) was probably secondary to the marked reducroborate the favourable long-term haemo-tion in pulmonary capillary pressure, reducing amic effects obtained in the present and the extravascular fluid volume and the stiffness vious studies (Fitzpatrick et al, 1983; Levine of the lungs. Spurious reduction of the filling l., 1984).…”
mentioning
confidence: 45%
“…The pooled hypertension (Rich et al, 1982). The reduction ilts from the international pilot studies on in pulmonary resistance in the present study lapril in congestive heart failure ( Figure 8) was probably secondary to the marked reducroborate the favourable long-term haemo-tion in pulmonary capillary pressure, reducing amic effects obtained in the present and the extravascular fluid volume and the stiffness vious studies (Fitzpatrick et al, 1983; Levine of the lungs. Spurious reduction of the filling l., 1984).…”
mentioning
confidence: 45%
“…According to Cohn et al (15), vasodilators are effective not only in chronic heart failure but also in acute heart failure following myocardial infarc tion. Moreover, it was demonstrated that several ACE inhibitors were effective in ALVF induced in experimental animals by coronary embolization (4)(5)(6). Therefore, us ing a similar animal model of ALVF, we eval uated the action of benazeprilat, a new potent and long acting ACE inhibitor with no direct inotropic effect (7,11,16), on acute heart fail ure.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown the efficacy of these agents in chronic (2,3) and acute car diac failure (4).…”
mentioning
confidence: 99%
“…Full details of the protocol have been described before (Fitzpatrick et al, 1983). In brief a 2-day control period was followed by 3 days of enalapril therapy, 5, 10 and 20 mg given at 09.00 h on days 3, 4 and 5 respectively.…”
Section: Short-term Studymentioning
confidence: 99%
“…Enalapril has beneficial haemodynamic effects, at least in the short term (Fitzpatrick et al, 1983). Although information is available from studies in normal volunteers and essential hypertensives, little is known of drug levels and plasma converting enzyme activity in patients with heart failure during the introduction of enalapril.…”
Section: Introductionmentioning
confidence: 99%